The perils of high carbohydrate drinks in the undiagnosed diabetic patient. (15th August 2011) - Saeed, Saad Aldeen; Hameed, Asjad; Yousif, Saif; Lessan, Nader
Abstract : Diabetes mellitus is increasing in its incidence and prevalence. Reduction in refined carbohydrate (sugar) intake is an important part of nutritional advice to patients with known diabetes. Sugar is available in a variety of confectionary products. It is also available in especially packaged 'convenience foods' as high energy drinks. Among people without diabetes, such food can have its own health risks. A significant group of patients with diabetes remain undiagnosed. This group are at especially high risk from all the negative metabolic effects of high sugar intake available as high calorie drinks. The authors report two patients without previously known diabetes who presented similarly with marked hyperglycaemic states, leading to severe metabolic disturbances. Both were obese, had common precipitating factors and consumed large quantities of sugary soft drinks ('lucozade'). Both patients recovered well. They were followed up for over 7 years. One is not diabetic and the second is diabetic requiring a small dose of metformin.